Isolation of heat shock promoter HSP18.2 from Arabidopsis thaliana and application in recombinant protein expression - Mai, Nguyen Chi; Van, Nguyen Tuong; Linh, Tran My; Lien, Le Quynh (Academia Journal of Biology, 2015)
Promoter locating upstream on a DNA-coding sequence initiates transcription of a particular gene. Therefore, promoter plays a vital role in controlling the expression of recombinant proteins in Molecular Farming. In this study, the heat shock promoter HSP18.2 calling AtHSP18.2-promoter was isolated from Arabidopsis thaliana. The nucleotide sequence of AtHSP18.2-promoter is 100% homology with nucleotide sequences of two other promoters (Acc.No X17295.1 and AB006705.2). The heat shock elements HSP of these sequences are conserved, meaning the functional of the isolated sequence as an heat shock promoter. Vector pXK7FNF2.0/HSP18.2 was designated containing the coding sequence of Green fluorescent protein GFP under the control of AtHSP18.2-promoter and transferred into cultured tobacco cell BY-2. The condition of 37°C/2h was identified as the optimal temperature for heat shock induction. Additionally, the expression of HA1 of avian A/H5N1 virus was sucessfully controlled by promoter AtHSP18.2-promoter. In this study we have demonstrated for the first time the isolation and application in controlling recombinant protein expression of an heat shock AtHSP18.2-promoter. This is the basis for further investigation in production of significant proteins using BY-2 cells.